Design and Build a Temperature and Humidity Monitoring System Using Arduino IoT Cloud with ESP32 as an IoT-Based Learning Medium - Roynaldo Siahaan; Faiza Rini; Herisvan Hendra (Journal of Practice Learning and Educational Development, 2026)
The objectives of this study are: (1) to design and develop an IoT-based temperature and humidity monitoring system in a wire house, (2) to implement an automatic spraying system that operates based on predetermined temperature and humidity parameters, and (3) to integrate the ESP32 microcontroller with sensors and actuators into the Arduino IoT Cloud platform so that the system can be monitored and controlled online. This research employs an applied quantitative approach with an experimental method. The study was conducted in August 2025 at the Wire House of SMK Negeri 1 Talamau. Data collection was carried out by testing the DHT22. The data analysis technique consisted of processing the measurement results of temperature and humidity obtained from the DHT22 sensor and the reference thermo-hygrometer (Humidity Temperature Clock-1). The results indicate that the IoT-based temperature and humidity monitoring system using Arduino IoT Cloud with ESP32 was successfully tested and performed well. The system was designed to allow easy real-time monitoring of room temperature and humidity through IoT technology, with real-time data accessible via laptop or smartphone, particularly Android devices. The findings show that the average relative error for temperature measurements was 1.12%, while the average relative error for humidity measurements was 2.07%. The average measured temperature using the DHT22 sensor was 34.68°C, compared to 34.27°C using the reference instrument. Meanwhile, the average humidity recorded by the DHT22 sensor was 67.04%, compared to 65.68% from the reference instrument.